Investigating the mechanisms of dissolved organic matter protection against copper toxicity in fish of Amazon's black waters - Crémazy, Anne; Braz-Mota, Susana; Brix, Kevin V.; Duarte, Rafael M. [UNESP]; Val, Adalberto L.; Wood, Chris M. (Elsevier, 2022)
We investigated how natural dissolved organic matter (DOM) of the Rio Negro (Amazon) affects acute copper (Cu) toxicity to local fish: the cardinal tetra (Paracheirodon axelrodi) and the dwarf cichlid (Apistogramma agassizii). It is established that Cu2+ complexation with DOM decreases Cu bioavailability (and thus toxicity) to aquatic organisms, as conceptualized by the Biotic Ligand Model (BLM). However, we also know that Rio Negro's DOM can interact with fish gills and have a beneficial effect on Na+ homeostasis, the main target of acute Cu toxicity in freshwater animals. We aimed to tease apart these potential protective effects of DOM against Cu-induced Na+ imbalances in fish. In the laboratory, we acclimated fish to Rio Negro water (10 mg L−1 DOC) and to a low-DOM water (1.4 mg L−1 DOC) with similar ion composition and pH (5.9). We measured 3-h Cu uptake in gills and unidirectional and net Na+ physiological fluxes across a range of Cu concentrations in both waters. Various DOM pre-acclimation times (0, 1 and 5 days) were evaluated in experiments with P. axelrodi. Copper exposure led to similar levels of net Na+ loss in the two fish, but with distinct effects on Na+ influx and efflux rates reflecting their different ionoregulation strategies. Rio Negro DOM protected against Cu uptake and toxicity in the two fish species. Both Cu uptake in fish gills and Na+ regulation disturbances were relatively well predicted by the modelled aqueous free Cu2+ ion concentration. These findings suggest that protection by DOM occurs mainly from Cu complexation under the tested conditions. The prevalence of this geochemical-type protection over a physiological-type protection agrees with the BLM conceptual framework, supporting the use of the BLM to assess the risk of Cu in these Amazonian waters.
Keywords: Apistogramma agassizii; Copper-gill binding; Dissolved organic carbon; Paracheirodon axelrodi; Rio Negro; Sodium fluxes